Child abuse and automatic emotion regulation in children and adolescents - Kim, Stephanie Gyuri; Weissman, David G.; Sheridan, Margaret A.; McLaughlin, Katie A. (Development and psychopathology, 2023)
Child abuse is associated with elevated risk for psychopathology. The current study examined the role of automatic emotion regulation as a potential mechanism linking child abuse with internalizing psychopathology. A sample of 237 youth aged 8–16 years and their caregivers participated. Child abuse severity was assessed by self-report questionnaires, and automatic emotion regulation was assessed using an emotional Stroop task designed to measure adaptation to emotional conflict. A similar task without emotional stimuli was also administered to evaluate whether abuse was uniquely associated with emotion regulation, but not cognitive control applied in a nonemotional context. Internalizing psychopathology was assessed concurrently and at a 2-year longitudinal follow-up. Child abuse severity was associated with lower emotional conflict adaptation but was unrelated to cognitive control. Specifically, the severity of emotional and physical abuse, but not sexual abuse, were associated with lower emotional conflict adaptation. Emotional conflict adaptation was not associated with internalizing psychopathology prospectively. These findings suggest that childhood emotional and physical abuse, in particular, may influence automatic forms of emotion regulation. Future work exploring the socioemotional consequences of altered automatic emotion regulation among youth exposed to child abuse is clearly needed.